Cover Picture: Highly Fluorescent Bipyrrole‐Based Tetra‐BF2 Flag‐Hinge Chromophores: Achieving Multicolor and Circularly Polarized Luminescence (Angew. Chem. Int. Ed. 27/2022). Issue 27 (21st June 2022) - Cui, Luxia; Shinjo, Hyuga; Ichiki, Takafumi; Deyama, Koichi; Harada, Takunori; Ishibashi, Kohei; Ehara, Takumi; Miyata, Kiyoshi; Onda, Ken; Hisaeda, Yoshio; Ono, Toshikazu
Abstract : Advancing the construction of circularly polarized luminescence (CPL) materials by molecular design has become an important target in this research area. In their Research Article (e202204358 ), Yoshio Hisaeda, Toshikazu Ono, and co‐workers demonstrate a new bipyrrole‐based boron difluoride family exhibiting intense multicolor luminescence with easy synthetic access. Tuning the rotational barrier around the 2, 2′‐bipyrrole affords CPL, and multicolor CPL can be achieved by controlling the aggregation state.